SOCIODEMOGRAPHIC AND PSYCHOLOGICAL CORRELATES OF SCHOOL ACHIEVEMENT - Šarčević, Dušana; Vasić, Aleksandar (Primenjena psihologija, 2014)
Many research studies bring validity of school achievementmeasured by teachers’ grade average in doubt. In orderto investigate that issue, three sets of data were analysed.Sociodemographic characteristics and data about schoolachievement in first semester were registered. Also, differentsets of questionnaires for measuring academic motivation,achievement motivation, personality traits, alienation and locusof control were applied. The study included three samples of 780,534 and 424 subjects of both sexes (50, 48, and 67% females).Respondents in first two samples were primary school pupils (10to 15 years) and in third sample secondary school pupils (15 to19 years). Hierarchical multiple regression analysis showed thatgender, parents’ education and work status, personality traits,and motivation explained from 7% to 31% variance of schoolachievement. The biggest portion of variance was explainedby sociodemographic characteristics, less by personality traits,and the smallest by the dimensions of motivation. In youngerrespondents the biggest partial contributions had genderand parents’ education, while in older ones only gender wasa significant correlate. It can be concluded that in averagepersonality traits explain less variance of school achievementamong which the most important are the traits that indicate socialadaptation and conformity. Partial contribution of academicmotivation was the smallest. Introjected and instrumentalaspects of motivation had significant partial contributions, whileinstrinsic motivation did not have any significance. Based onthe results, it can be said that school achievement measuredas average grade is a problematic indicator of school successbecause it depends more on sociodemographic characteristicsthan on personality traits and motivation.